Macrobenthic composition of the southeast continental shelf of India. (28th January 2014) - Manokaran, Seerangan; Khan, Syed Ajmal; Lyla, Parameswari S.
Abstract Macrobenthic faunal composition was studied at six different depth ranges (30–50, 51–75, 76–100, 101–150, 151–175 and >176 m) in five transects (off Karaikkal, Parangipettai, Cuddalore‐SIPCOT, Cheyyur and Chennai) in the continental shelf of southeast coast of India. Eleven diverse taxa were found, comprising 113 species of polychaetes, 14 species of bivalves, 10 species of amphipods and 'others' (five tanaids, five crabs, four isopods, three echinoderms, two shrimps, two cnidarians, two fishes and one cephalochordate). Polychaetes were the dominant taxa, constituting 88.5% of the total abundance and 30.7% of the total biomass. The number of species (seven per 0.2 m2 at >176 m depth range in Chennai to 46 per 0.2 m2 at 30–50 m in Cheyyur), abundance (216 per 0.2 m2 at >176 m in Karaikkal to 353 per 0.2 m2 at 30–50 m in Cheyyur) and biomass (0.09 g per 0.2 m2 at 151–175 m in Karaikkal and 4.6 g per 0.2 m2 at 30–50 m in Cheyyur) of macrobenthos decreased with increase in depth. DO decreased gradually from 30 m depth; beyond 150 m, the decrease was pronounced due to the presence of the oxygen minimum zone. Using the distance based linear model (DISTLM), it was found that the environmental variables explained about 73.3% of the total variability in macrofaunal distribution. The heavy metals cobalt and mercury, as well as water pressure (proxy for depth), showed a significant relationship with macrofauna, explaining respectively 9, 7.3 and 7% of the total variability. The contribution of other variables was smaller.